Investigation of Allergic Sensitizations in Children With Allergic Rhinitis and/or Asthma - Dai, Lingman; Liu, Jinling; Zhao, Qi; Li, Mengyao; Zhou, Yunlian; Chen, Zhimin; Zhang, Yuanyuan (Frontiers in Pediatrics, 2022)
Objective: Allergic rhinitis (AR) and asthma are becoming one of the most prevalent diseases in children. Identifying sensitization to aeroallergens is seemed to be valuable for diagnosing allergic disease and guiding its treatment. This study aimed to analyze the profiles of sensitization to aeroallergen in children with AR and/or asthma by SPT, and explore the differences of sensitization between different kind of allergic disease, different gender and different age. Methods: A total of 230 children with AR and/or asthma who were hospitalized in our hospital from June 2017 to September 2019 were eligible in this retrospective study. All patients completed standardized questionnaires and skin prick test (SPT). Based on the gender, age or classification of allergic disease, the sensitizations to 13 aeroallergens were compared. Results: Of the 230 patients, 67.4% of enrolled were positive for SPT, the top 5 allergens were Dermatophagoides pteronyssinus (Der.p) (59.3%), Dermatophagoides farina (Der.f) (58.7%), Blomia tropicalis (Blot.) (40.3%), dog hair (36.1%), Blattella germanica (20.4%), respectively. More than 90% of patients were sensitized to two or more allergens. As to the effect of age on aeroallergens, we found that the sensitizations of Blot., dog fur and multiple sensitization (≥5 allergens) were more common in adolescence (P<0.01, P<0.05). Regarding gender, we found the positive rate of SPT and the percentages of double allergen-sensitizations in boys was much higher than girls (P<0.01, P<0.01), and the positive rate to Der.p, Der.f and ragweed were also significantly higher in boys (P<0.01, P<0.05, P<0.05, respectively). Furthermore, we found the asthma-rhinitis multimorbidity increased the incidences of sensitizations, patients with AR and asthma had significantly higher positive rates to Der.p and Der.f when compared to the AR or asthma group (P<0.05, P<0.05). Conclusion: Allergic sensitizations were common in children with allergic rhinitis and/or asthma, gender, age and asthma-rhinitis multimorbidity might affect the prevalence of sensitizations to aeroallergens.